Mass of Malam Jumat Kliwon at Sendang Sriningsih: Sociological and Theological Insights - Dominikus Setio Haryadi; Antonius Galih Arga Wiwin Aryanto (Universitas Sanata Dharma, 2023)
This research was conducted using qualitative methods. The method taken is to conduct interviews with 3 sources. This research is motivated by the author's interest in the Kliwon Friday night Mass at the Sendang Sriningsih Maria Cave, Dalem, Klaten. The author feels that the Kliwon Friday night Tirakatan Mass is a form of inculturation in the Catholic Church, specifically for Catholicism in the Sriningsih area. In this research, the author wants to look at the meaning of the Kliwon Friday night Mass for the people in Sriningsih. The theoretical framework that the author takes is to use the Javanese philosophy of life according to Suwardi Endraswara's book, Querida Amazonia Document which deals with inculturation, also from Gaudium et Spes which talks about the relationship of evangelism with culture. This research produces data that the people really feel the sincerity and solemnity of the Tirakatan Kliwon Friday Mass, even though there is no special ritual in the celebration. The absence of special rituals is not a barrier for people to meet and find God.